(untitled) (Castilla. Estudios de Literatura, 2013)
The imaginary approach Azorín’s work encourages us to believe in a constant emotional core, prior to his texts, and involved in the creative process. On this basis we analyze one of the most beloved works by Azorín: Al margen de los clásicos. From it we draw the images and relevant affective tendencies manifested in profound content according to the imaginary universality at different regimes of the image, and emotional uniqueness of creative sensibility. The passage of time and death constitute the backbone of an imaginary feeling that seeks to counter the negative effects of this feeling and rescue the most pure and authentic human spirit, individual and collective. Al margen de los clásicos confirms affective and imaginary unity that precedes and unites the various writings of Azorín.